PERANCANGAN APLIKASI PERSEDIAAN SPAREPART BERBASIS WEB MENGGUNAKAN CMS LARAVEL PADA (PT. NASIONAL MCPUMPS INDONESIA JAKARTA PUSAT) - Romy Ramadhan; Mochamad Adhari Adiguna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. National Mcpumps Indonesia is a business engaged in the sale of water pumps with its address in Central Jakarta where the target market is all people. Data processing at PT. National Mcpumps Indonesia is still done manually such as creating customer data, entering spare parts data, leaving spare parts data, ordering data, spare parts data all still in the form of document archives where such storage makes archives pile up. Therefore we need an application system that can store this important data. In supporting effective and efficient spare part inventory data processing, it is necessary to design an application to help process the required calculation data to be more accurate and save time. In this study, the author uses a prototype software development method and modeling using the Unified Model Language (UML). And for making the website the author uses the PHP programming language with MySQL as database management. Therefore, the author tries to make an application to be able to process and store data quickly and precisely. To help Entrepreneurs develop to increase sales, if sales activities are managed properly.